Sexual Self-Esteem and Psychological Burden of Adults With Neurofibromatosis Type 1 - Leidger, Anna; Vosschulte, Marie; Nieder, Timo O.; Mautner, Victor-Felix (Frontiers in Psychology, 2022)
Neurofibromatosis type 1 (NF1) is one of the most common tumor predisposition syndromes which primarily affects the skin. NF1 is characterized by various degrees of skin tumors and pigmentation abnormalities such as café-au-lait macules. Other skin diseases, such as psoriasis or neurodermatitis, have a negative influence on sexuality and quality of life and represent a psychological burden for those affected. The present study investigated the extent to which skin tumors (disfigurement) are related to sexuality and psychosocial factors in NF1 individuals. An anonymous online survey was carried out on Facebook and the webpage of the German Neurofibromatosis Association and a total of 166 persons participated. Of these participants, 92 were affected by NF1.74 healthy persons took part in the survey as a comparative group. Results show a significant relation between sexuality, body image, quality of life and the presence of depressive symptoms of the NF1 affected persons. Individuals with NF1 show a more negative sexual self-esteem. These concerns should be taken into account in NF1- related health care approaches.